IFNL3 rs12980275 Polymorphism Predicts Septic Shock-Related Death in Patients Undergoing Major Surgery: A Retrospective Study - Pérez-García, Felipe; Jiménez-Sousa, Maria Ángeles; Soria, Susana; Jorge-Monjas, Pablo; Fernández-Rodríguez, Amanda; Gómez-Sánchez, Esther; Heredia-Rodríguez, María; Gómez-Pesquera, Estefanía; Martínez-Paz, Pedro; Tamayo, Eduardo; Resino, Salvador (Frontiers in Medicine, 2020)
Interferon lambda 3 (IFNL3, previously called IL-28B) is a cytokine with effects against viral and bacterial pathogens. We aimed to analyze the IFNL3 rs12980275 SNP in patients who underwent major surgery, in order to establish its relationship with susceptibility to septic shock and septic shock-related death in these patients. We performed a case-control study on 376 patients to establish the association between IFNL3 rs12980275 SNP and the susceptibility to develop septic shock. Besides, we performed a longitudinal study among 172 septic shock patients using survival analysis with one censoring point of 28-days mortality. The IFNL3 rs12980275 polymorphism was genotyped by Agena Bioscience’s MassARRAY platform. IFNL3 rs12980275 polymorphism was not associated with higher susceptibility to infection and septic shock development. Regarding survival analysis, the Kaplan-Meier analysis showed that patients with IFNL3 rs12980275 AA genotype had higher survival than patients with GG genotype (p= 0.003). The Cox regression analysis adjusted by the most relevant clinical and epidemiological characteristics showed that the GG genotype (recessive model) and the presence of the G allele (additive model) were associated with higher risk of death (adjusted hazard ratio (aHR)= 2.15, p= 0.034; aHR= 1.50, p= 0.030, respectively). In conclusion, IFNL3 rs12980275 polymorphism was associated with septic shock-related death in patients who underwent major surgery. The A allele was linked to protection, and the G allele was associated with an increased risk of death. This is a first preliminary study, which suggests that IFNL3 polymorphisms could play a central role in sepsis pathogenesis.